Impact of trypanosomiasis on African agriculture - Swallow, B.M. (OAU/STRC, 1999)
African animal trypanosomosis constrains agricultural production in areas of Africa that hold the continent's greatest potential for expanded agricultural production. Previous studies indicate that the incidence of trypanosomosis: (i) reduces calving rates by 1-12 percent in tolerant breeds and by 11-20 percent in susceptible breeds of cattle; (ii) increases calf mortality by 0-10 percent in tolerant breeds and by 10-20 percent in susceptible breeds of cattle; (iii) reduces milk offtake from trypanotolerant cattle by 10-26 percent; and (iv) reduces lambing and kidding rates by 4-38 percent. At the herd level, it is estimated that the incidence of trypanosomosis reduces cattle offtake by 5-30 percent, milk offtake by 10-40 percent, and the work performance of oxen by 33 percent. The risk of trypanosomosis also shapes farmers choices about livestock purchases, sales and overall herd size. The evidence from a small number of field studies suggests that farmers in areas of high trypanosomosis also shapes farmers choices about livestock purchases, sales and overall herd size. The evidence from a small number of field studies suggests that farmers in areas of high trypanosomosis risk keep 25-60 percent as many cattle as farmers in nearby areas of low risk. Impacts on other livestock species vary greatly depending upon the management system and level of susceptibility. Overall it has been estimated that trypanosomosis reduces the density of cattle by 37 percent in the sub-humid zone and 70 percent in the humid zone. The indirect effects of trypanosomosis risk on land use and agricultural production can be inferred from focused field studies and aggregate-level studies that have examined the relationship between livestock and crop production more generally. In mixed farming systems where trypanosomosis is so severe that it constrains the number of oxen that farmers own, it can reduce the average area planted per household by as much as 50 percent. By generally constraining farmers from the overall benefits of livestock to farming -- less efficient nutrient cycling, less access to animal traction, lower income from milk and meat sales, less access to liquid capital -- trypanosomosis reduces both yields and areas cultivated. It is estimated that the elasticity of livestock stock with respect to total agricultural production is about 0.20: a 50 percent reduction in livestock population would reduce the total production of agricultural output by 10 percent.